Performance of Molecular Breast Imaging as an Adjunct Diagnostic Tool - Shermis, Robin B; Redfern, Roberta E; Bazydlo, John; Naimy, Gabriel; Kudrolli, Haris; Chen, John (Translation: The University of Toledo Journal of Medical Sciences, 2019)
Purpose: The aim was to retrospectively assess the performance of molecular breast imaging (MBI) as an adjunct diagnostic tool when symptoms could not be explained by conventional imaging, or when mammography or ultrasound findings were equivocal. Methods: The analysis was comprised of women who underwent further testing with MBI after diagnostic mammography and/or targeted ultrasound. Outcome measures included sensitivity, specificity, and positive and negative predictive values. Receiver-operating characteristic (ROC) curve was constructed and analyzed as a performance measure. Results: In 301 women with a complete reference standard, 18 (6.0%) were diagnosed with cancer. MBI detected cancer in 16 subjects; two interval cancers occurred. 15 of the 16 cancers detected by MBI were invasive. Overall sensitivity of MBI in this sample was 88.9 % (95% CI 65.6 – 98.6), with 97.5% specificity (95% CI 95.0 – 99.0). Positive predictive value (PPV) was 69.6%, while negative predictive value for recall (NPV) was calculated as 99.3%. ROC curves demonstrated excellent performance (area under the curve = 0.933). Conclusions: MBI is a valuable diagnostic tool for further evaluation or to guide management when conventional imaging is incomplete. The majority of tumors in this study were invasive carcinomas with node negative status, important for timely treatment.